1993
DOI: 10.1128/jvi.67.5.2552-2558.1993
|View full text |Cite
|
Sign up to set email alerts
|

A common neutralizing epitope conserved between the hemagglutinins of influenza A virus H1 and H2 strains

Abstract: When mice were immunized with the A/Okuda/57 (H2N2) strain of influenza virus, a unique monoclonal antibody designated C179 was obtained. Although C179 was confirmed to recognize the hemagglutinin (HA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
262
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(271 citation statements)
references
References 46 publications
2
262
0
Order By: Relevance
“…Reciprocally, inhibition of NA activity by oseltamivir was shown to boost NKp46 recognition and killing of infected cells [71] a finding that might explain the 64 Antiviral strategies [20,23]. (b) Anti-stem antibodies (blue) interfere with the pH-driven HA rearrangement blocking the process of viral fusion in endosomes [41,56,57]. (c) Anti-head and anti-stem antibodies can inhibit the release of budding virions from infected cells [35,85].…”
Section: Current Opinion In Virologymentioning
confidence: 99%
See 1 more Smart Citation
“…Reciprocally, inhibition of NA activity by oseltamivir was shown to boost NKp46 recognition and killing of infected cells [71] a finding that might explain the 64 Antiviral strategies [20,23]. (b) Anti-stem antibodies (blue) interfere with the pH-driven HA rearrangement blocking the process of viral fusion in endosomes [41,56,57]. (c) Anti-head and anti-stem antibodies can inhibit the release of budding virions from infected cells [35,85].…”
Section: Current Opinion In Virologymentioning
confidence: 99%
“…The ten available X-ray structures ( Figure 1b 36-38,39 ,40 ] revealed that these antibodies can adopt multiple binding modalities to cope with high amino acid diversity and with the structural constraints posed by the presence of conserved Group-1 and Group-2-specific glycans. Despite the restricted propensity of the stem region to mutate, escape mutants have been isolated also for antistem antibodies [41,42 ], and their existence is also supported by the incomplete breadth of certain anti-stem antibodies, for example, the lack of binding to human H2N2 viruses by CR6261 [30]. Finally, a rare antibody, CR9114, was shown to bind to several influenza A and B viruses tested, although neutralizing activity was limited to influenza A [23].…”
Section: Overview On Broadly Neutralizing Antibodies Against Influenzmentioning
confidence: 99%
“…After 8 h of incubation, the infected cells were fixed with ethanol then reacted with the culture medium of individual hybridoma cell clones. As control antibodies, we used several murine MAbs, i.e., C43 to nucleoprotein (NP) of influenza A H3N2 virus [12], C179 to HA of H1N1 [12], F49 to HA of H3N2 (Okuno, unpublished), 9F3 to NP of influenza B virus [13], and 9E10 to HA of influenza B virus [14]. The cells were then reacted with fluores-cein isothiocyanate (FITC)-conjugated rabbit anti-human or antimouse antibodies (Jackson ImmunoResearch, Cambridgeshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Hemagglutinin-inhibition (HI) test. The HI test was carried out as described previously [12]. The culture medium of individual hybridoma clones was treated with receptor destroying enzyme (RDE).…”
Section: Methodsmentioning
confidence: 99%
“…However, strain-specific antibodies provide incomplete protection against antigenic drift variant viruses of the same subtype and provide no protection against different HA subtypes. In 1993, Okuno et al characterised a murine monoclonal antibody (C179) that cross-reacted with H1 and H2 but not H3 subtypes; 15 this antibody bound an epitope in the highly conserved HA stem. In the past decade, HA stem-reactive antibodies have been identified in humans.…”
Section: Introductionmentioning
confidence: 99%